2022
DOI: 10.1186/s12877-021-02732-7
|View full text |Cite
|
Sign up to set email alerts
|

Practice effect and test-retest reliability of the Mini-Mental State Examination-2 in people with dementia

Abstract: Background The Mini-Mental State Examination-Second Edition (MMSE-2) consists of three visions: a brief version (MMSE-2:BV), a standard version (MMSE-2:SV), and an expanded version (MMSE-2: EV). Each version was equipped with alternate forms (blue and red). There was a lack of evidence on the practice effect and test-retest reliability of the three versions of the MMSE-2, limiting its utility in both clinical and research settings. The purpose of this study was to examine the practice effect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…This study showed that the short, remote, and digital cognitive M-CogScore test was comparable with both the MMSE-2, which is an updated version of the original and widely administered MMSE cognitive screening test ( 3 ), and the CDR, which is a structured cognitive questionnaire without objective testing. These results are particularly noteworthy because short tests are usually considered to be inadequate to detect MCI ( 12 ).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…This study showed that the short, remote, and digital cognitive M-CogScore test was comparable with both the MMSE-2, which is an updated version of the original and widely administered MMSE cognitive screening test ( 3 ), and the CDR, which is a structured cognitive questionnaire without objective testing. These results are particularly noteworthy because short tests are usually considered to be inadequate to detect MCI ( 12 ).…”
Section: Discussionmentioning
confidence: 79%
“…While the CDR takes up to 60 min ( 5 , 19 , 30 ), and MMSE-2 takes 10–15 min to complete ( 3 ), the M-CogScore can be completed in less than 5 min ( 23 ). Additionally, although the CDR is used extensively in research trials and epidemiological studies to identify cognitively impaired individuals, it requires the presence of both a trained test-supervisor to administer and score, as well as the presence of a companion ( 31 ), which are not required for the M-CogScore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the same test was repeated three times over a certain period, similarly to previous studies. Therefore, the inclusion of learning and order effects may have affected the results [mean (standard deviation)] of the Mini-Cog scores at the time of participation in the study: in the beginning 4.2 (± 1.0); 4 weeks later: 4.8 (± 0.5); 8 weeks later: 4.6 (± 1.0) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%